THE EFFECT OF BALANCE, CONCENTRATION, AND COORDINATION ON DOLLYO CHAGI KICK SKILLS IN POPB TAEKWONDO ATHLETES IN DKI JAKARTA - Reggie Reginald; Fahmy Fachrezzy; Iwan Hermawan (Gladi : Jurnal Ilmu Keolahragaan, 2021)
The aim of this research was to determine the direct and indirect effect as well as the simultaneous effect of exogenous variables with endogenous variables. The research method used was an associative quantitative approach using test and measurement techniques. The data analysis technique used was a path analysis approach. The population in this research was all of POPB DKI Jakarta athletes in 2021 totaling 20 people. The sampling technique used was total sampling so that the number of samples in this research was 20 people consisting of 10 women and 10 men. The skills of Dollyo Chagi Kick Taekwondo used the Dollyo Chagi Kick skills test. The balance used a modified bass test. The concentration used a concentration grid test. The instrument of eye-foot coordination used a smart speed pro coordination test. The results showed that the direct effect of variable X1 on Y = 0,243. The direct effect of variable X2 on Y = 0,567. The direct effect of variable X3 on Y = 0,378. The direct effect of variable X1 on X3 = 0,706. The direct effect of variable X2 on X3 = 0,297. The indirect effect of variable X1 on Y through X3 = 0,706 x 0,378 = 0,267. The indirect effect of variable X2 on Y through X3 = 0,297 x 0,378 = 0,113.